(untitled) (Research, Society and Development, 2022)
Violence is a complex and deep-rooted, multifaceted phenomenon that affects all social groups, institutions and age groups. It is historical and affects men and women differently, since the female sex is significantly more affected. As it occurs preferentially in the domestic environment, it is seen by society as an individual problem of the couple or the woman who suffers violence and, many times, causes damage that remains with the victim throughout her life. Craniofacial pain stands out, chronic pain that affects facial structures. The literature describes a direct relationship between violence and the development and aggravation of chronic pain, however, few studies in the area of TMD and Orofacial Pain (OFP) have been carried out. Thus, the present study aimed to carry out an integrative review of texts already published on the subject, thus evaluating the impact of violence on the development of craniofacial pain in women.